A rare case of Ewing’s sarcoma in the sinonasal tract - Satish, Deepthi; R., Nandakumar; A. M, Balasubramanya; Mathew, Nitty (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Ewing's sarcoma (ES) first described by James Ewing in 1921, is a primary neoplasm of the skeletal system. Extraskeletal Ewing’s sarcoma (EES) is a rare, rapidly growing, round cell malignant tumour that can develop in the soft tissue at any location. Extraskeletal Ewings sarcoma of the head and neck is uncommon. Nearly 80% of patients are younger than 20 years with peak incidence in the second decade. Ewings sarcoma rarely affects the sinonasal tract. Diagnosis is after histopathological examination immunohistochemical studies and cytogenetic studies. Treatment will include a multidisciplinary approach with surgery as the first line followed by chemotherapy and radiotherapy. Ewings sarcoma in the head and neck region do not metastazise early hence carries a better prognosis. Evaluation of lesion using imaging, biopsy followed by histopathology and immunohistochemistry and cytogenetic analysis are necessary for early diagnosis and treatment. We present a case of an 18-year-old male patient with left sided epistaxis and left sided nasal obstruction, on examination a mass was seen the nasal cavity, endoscopic excision and biopsy of the mass was suggestive of an Ewings sarcoma. He received post-operative chemotherapy and radiotherapy. 2 years on regular follow up patient is fine without signs of metastasis or recurrence. We are presenting this case due to the rarity of its presentation in the sinonasal tract.